Daisy And The Trouble With Christmas - Gray, Kes (Random House Inc, 2009)
Daisy has been EXTREMELY excited about Christmas since September. And when Daisy is excited, TROUBLE will surely follow! Daisy loves the carols, the sparkly lights, the crackers, the snowmen, and especially the chance to be in the school Christmas play. She's got SEVEN whole words to learn! But when Daisy and her best friend Gabby decide the dolly their teacher has chosen to play the Baby Jesus is a bit . . . well, boring, Daisy comes up with a plan that will mean TROUBLE!
Keywords: Christmas & Advent; Holidays & Celebrations; Juvenile Fiction